2009
DOI: 10.1007/s12098-009-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

A community based approach to improve health care seeking for newborn danger signs in rural wardha, India

Abstract: The present approach improved mothers' knowledge regarding newborn danger signs and improved their health care seeking behavior for newborn danger signs at community level. Due to lack of faith in government health services, women preferred to seek care from private providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 7 publications
1
72
0
Order By: Relevance
“…This finding is consistent with the findings in peri urban Wardha, India (2008) [16] which was reported by 76.4%, Luck know City India (2006) [17] which was reported by 76.9%, Ghana (2013) [18], and in the previous study in 4 regions of Ethiopia (2012) [15] which was reported by 83.6% of the mothers. "Poor sucking" is also found to be among the three most commonly reported neonatal danger signs in this study, which is reported by 42.0% of mothers which is in agreement with findings in the study conducted in Lucknow city, India (2006) [17] which was reported by 68.9%, rural Waldha, India (2007) [19] which was responded with 61.6%, Bangladesh (2007) [20] which was responded with 56%, and Ghana (2013) [21] and Ethiopia (2012) [22] which was responded by 39.5%. This study also found that "umbilical redness", "eye redness or discharge" and "yellow palms/sole, eye" are the least known neonatal danger signs which was responded by Ç 5% of mothers.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with the findings in peri urban Wardha, India (2008) [16] which was reported by 76.4%, Luck know City India (2006) [17] which was reported by 76.9%, Ghana (2013) [18], and in the previous study in 4 regions of Ethiopia (2012) [15] which was reported by 83.6% of the mothers. "Poor sucking" is also found to be among the three most commonly reported neonatal danger signs in this study, which is reported by 42.0% of mothers which is in agreement with findings in the study conducted in Lucknow city, India (2006) [17] which was reported by 68.9%, rural Waldha, India (2007) [19] which was responded with 61.6%, Bangladesh (2007) [20] which was responded with 56%, and Ghana (2013) [21] and Ethiopia (2012) [22] which was responded by 39.5%. This study also found that "umbilical redness", "eye redness or discharge" and "yellow palms/sole, eye" are the least known neonatal danger signs which was responded by Ç 5% of mothers.…”
Section: Discussionsupporting
confidence: 90%
“…[17] Community mobilization and participatory, need based health education strategy based on local epidemiology and caregivers perspectives could improve health care seeking for newborn danger signs in rural Wardha. [18] Hence, along with the initial two components of IMCI strategy (improving the skills of health workers and improving health system), the third component of IMCI strategy i.e. household and community IMCI (HH/C IMCI) strategy should be implemented through community participation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we need to enhance homebased newborn care, which has been shown to improve mothers' knowledge regarding danger signs and subsequent healthcare seeking. 58 Nevertheless, narratives available in VA forms showed the presence of vague symptoms rather than clearcut danger signs before neonatal deaths in many cases, which highlights the importance of routine preventive care of all neonates rather than care of only sick neonates.…”
Section: Open Accessmentioning
confidence: 99%